Peningkatan Hasil Belajar Lari Jarak Pendek dengan Metode Permainan Ninja Tictactoe pada Siswa Sekolah Dasar - Aji, Bayu Purnomo; Priambodo, Anung; Suroto, (Jurnal Didaktika Pendidikan Dasar, 2025)
Short distance running is one of the parameters to measure physical activity part, which is speed that serves as a support for the body to move to another point in a short time and not experience significant fatigue. This study aims to determine the effectiveness of increasing the speed of short-distance running of grade V students with the ninja tictactoe approach. The method used in this study was classroom action research carried out during the II cycle, the subjects of this study consisted of 19 male and 16 female of grade V students of Penjaringan sari 1 elementary school. Researchers collected data using pretest and posttest which is assisted by the TKSI speed measuring instrument and then converted into a value. The results of the student's condition before the action was carried out had an average score of 20 and increased to 24 in cycle I, then in cycle II students had an initial condition of average score of 56 then increased to 82.86. It can be concluded that using ninja tictactoe games can help students improve physical activity part of speed short distance running 40 meters in phase C elementary school.